Asymmetric Catalysis in Liquid Confinement: Probing the Performance of Novel Chiral Rhodium–Diene Complexes in Microemulsions and Conventional Solvents. Issue 40 (24th June 2019) - Deimling, Max; Kirchhof, Manuel; Schwager, Barbara; Qawasmi, Yaseen; Savin, Alex; Mühlhäuser, Tina; Frey, Wolfgang; Claasen, Birgit; Baro, Angelika; Sottmann, Thomas; Laschat, Sabine
Abstract: The role of liquid confinement on the asymmetric Rh catalysis was studied using the 1, 2‐addition of phenylboroxine (2 ) to N ‐tosylimine1 in the presence of [RhCl(C2 H4 )2 ]2 and chiral diene ligands as benchmark reaction. To get access to Rh complexes of different polarity, enantiomerically pure C2 ‐symmetric p ‐substituted 3, 6‐diphenylbicyclo[3.3.0]octadienes4 and diastereomerically enriched unsymmetric norbornadienes5 and6 carrying either the Evans or the SuperQuat auxiliary were synthesized. A microemulsion containing the equal amounts of H2 O/KOH and toluene/reactants was formulated using the hydrophilic sugar surfactant n ‐octyl β‐d ‐glucopyranoside (C8 G1 ) to mediate the miscibility between the nonpolar reactants and KOH, needed to activate the Rh–diene complex. Prominent features of this organized reaction medium are its temperature insensitivity as well as the presence of water and toluene‐rich compartments with a domain size of 55 Å confirmed by small‐angle X‐ray scattering (SAXS). Although bicyclooctadiene ligands4 a, b, e performed equally well under homogeneous and microemulsion conditions, ligands4 c, d gave a different chemoselectivity. For norbornadienes5, 6, however, microemulsions markedly improved conversion and enantioselectivity as well as reaction rate, as was confirmed by kinetic studies using ligand5 b . Abstract : Improved reaction rate and enantioselectivity was realized when microemulsions stabilized by the hydrophilic sugar surfactant n ‐octyl β‐d ‐glucopyranoside (C8 G1 ) containing a Rh‐chiral diene complex and equal amounts of H2 O/KOH and toluene/reactants replaced conventional solutions in asymmetric 1, 2‐additions of phenylboroxine (2 ) to N ‐tosylimine1 . The norbornadiene ligands differ in the substitution pattern and oxazolidinone unit.